2004
DOI: 10.1021/bp049792h
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Candida bombicola Cells on Free-Standing Organic-Gold Nanoparticle Membranes and Their Use as Enzyme Sources in Biotransformations

Abstract: Preparation of chemically functionalized biocompatible surfaces is of current interest, with application in the immobilization of various bioactive species such as DNA, enzymes, whole cells, etc. We report herein the one-step synthesis of a self-supporting gold nanoparticle membrane, its surface modification, and application in the immobilization of Candida bombicola (yeast) cells. The gold nanoparticle membrane is prepared by the spontaneous reduction of aqueous chloroaurate ions by a diamine at a liquid-liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The partial mass spectrum of the hydroxylated fatty acids released from the sophorolipids was compared with standard 20-HETE mass spectrums (data not shown). Figure Phadtare et al 2004). The mass spectrum thus clearly indicated the hydroxyl group at the C20 position and the compound was 20-hydroxy-5Z,8Z,11Z,14Z-eicosatetraenoic acid (20-HETE).…”
Section: Gc-msmentioning
confidence: 99%
See 2 more Smart Citations
“…The partial mass spectrum of the hydroxylated fatty acids released from the sophorolipids was compared with standard 20-HETE mass spectrums (data not shown). Figure Phadtare et al 2004). The mass spectrum thus clearly indicated the hydroxyl group at the C20 position and the compound was 20-hydroxy-5Z,8Z,11Z,14Z-eicosatetraenoic acid (20-HETE).…”
Section: Gc-msmentioning
confidence: 99%
“…Liberated hydroxyfatty acids were purified on 500 mg Aminopropyl Sep-Pak Cartridges (Waters) as described by Prabhune et al (2002) and Phadtare et al (2004). The isolated hydroxyeicosatetraenoic acids were methylated with diazomethane and silylated according to MacLauf and Rigaud (1982) using trimethylchlorosilane.…”
Section: Analysis Of Sophorolipids By Tlcmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, these hybrid systems can enhance one or both of the functions of its components; for example, it was previously shown that plasmonic nanoparticles enhance the electro-catalytic response of a glucose oxidase system (glucose biosensor)[1] and the detection of various analytes of interest, such as hydrogen peroxide and uric acid [2], thiocholine [3], carcinoembryonic antigen [4] and DNA [5]. Several strategies for the immobilization of enzyme on plasmonic structures have been developed: layer-by-layer assembly[6], self-assembled monolayers[7], protein-antigen interactions[8], covalent attachment[9] and sol-gels[10]. Despite the existence of wide range of studies on enzyme/nanoparticle hybrids, the comparison of enzyme immobilization strategies and the effect of nanoparticle loading on surfaces on enzymatic activity were never reported.…”
Section: Introductionmentioning
confidence: 99%
“…This research group has recently shown that Yarrowia lipolitica [156] and Candida bombicola yeast cells [157] can be immobilized on patterned hydrophobic regions of thermally evaporated fatty lipid films. In the latter case, the enzyme cytochrome P450 present in the yeast cells was used to catalyze in situ ö and ö-1 hydroxylation of arachidonic acid (AA).…”
Section: Immobilization Of Whole Cells On Nanostructured Polymersmentioning
confidence: 99%